2018
DOI: 10.1177/0305735618778126
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence, alexithymia, stress, and people’s reasons for listening to music

Abstract: Emotional intelligence, alexithymia, stress and peoples' reasons for listening to musicWord count: 5,395 excluding tables and references Emotional intelligence & music 2 AbstractThe present study investigated the relationship between people's reasons for listening to music, trait emotional intelligence and alexithymia whilst also controlling for the effect of participants' gender, age and perceived stress levels. In keeping with previous research, initial findings indicated that emotionally intelligent individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Ratings of music's ability to obtain all these goals were no different across genders. This is consistent with studies that found only negligible differences in music use as a function of gender (Schäfer and Sedlmeier, 2009;Ter Bogt et al, 2011), although other studies did find some such differences (Lonsdale and North, 2011;Kuntsche et al, 2016;Greb et al, 2018;Gupta, 2018;Lonsdale, 2019). These discrepant results may stem from the type of function under consideration: while the studies that found gender differences focused on arousal, dance, social bonds, expression of emotions at various points along the lifespan, the current study focused on more abstract and general goals as they related to wellbeing during the lockdown.…”
Section: Music Is the Most Efficient Activity In Obtaining Diverse Wellbeing Goals Across Age Gender And Culturesupporting
confidence: 87%
See 1 more Smart Citation
“…Ratings of music's ability to obtain all these goals were no different across genders. This is consistent with studies that found only negligible differences in music use as a function of gender (Schäfer and Sedlmeier, 2009;Ter Bogt et al, 2011), although other studies did find some such differences (Lonsdale and North, 2011;Kuntsche et al, 2016;Greb et al, 2018;Gupta, 2018;Lonsdale, 2019). These discrepant results may stem from the type of function under consideration: while the studies that found gender differences focused on arousal, dance, social bonds, expression of emotions at various points along the lifespan, the current study focused on more abstract and general goals as they related to wellbeing during the lockdown.…”
Section: Music Is the Most Efficient Activity In Obtaining Diverse Wellbeing Goals Across Age Gender And Culturesupporting
confidence: 87%
“…Music was found to be most efficient at attaining the goal of enjoyment and maintaining a good mood. This goal was also most often cited by participants in studies of music-use as the most important reason for listening to music (Juslin and Laukka, 2004;Zentner et al, 2008, Schäfer andSedlmeier, 2009;Ter Bogt et al, 2011;Lonsdale, 2019). However, note that what we measure is the perceived efficiency of music to obtain this goal-therefore drawing one step closer to the connection between music and the functions it is assumed to fulfill.…”
Section: Music Is the Most Efficient Activity In Obtaining Diverse Wellbeing Goals Across Age Gender And Culturementioning
confidence: 85%
“…Second, different types of media consumption have been shown to relate in different ways to wellbeing outcomes. For instance, people often listen to music in order to self-regulate their mood ( Lonsdale and North, 2011 ; Boer and Fischer, 2012 ; Schäfer, 2016 ; Baltazar et al, 2019 ; Lonsdale, 2019 ), reduce negative emotional states ( North et al, 2004 ; Sloboda, 2010 ), and help relieve or manage everyday stress ( Laukka, 2007 ; Krause et al, 2020 ). Findings regarding the benefits of watching TV/films and using social media are more mixed (e.g., Frey and Benesch, 2008 ; Cuñado and Pérez de Gracia, 2012 ; Arampatzi et al, 2016 ; Groshek et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…It seems as though EI is related to music listening (Londsdale, 2018). Many people listen to music to control their emotional state (Londsdale and North, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, these individuals must have a greater level of recognition and management of their own emotions. In other words, they need to have developed EI, with the use of music depending, in part, on the level of EI acquired (Londsdale, 2018).…”
Section: Introductionmentioning
confidence: 99%